Impact of waterpipe smoking on the salivary microbiome - Senaratne, Nikitha Lalindri Mareena; Chong, Chun Wie; Yong, Lim Shu; Yoke, Ling Fong; Gopinath, Divya (Frontiers in Oral Health, 2023)
Background While oral mirobial dysbiosis due to tobacco smoking has been studied thoroughly, there is limited data on the effect of waterpipe smoking on the oral microbiome. This study aims to compare the salivary microbiome between waterpipe smokers and non-smokers. Materials and methods Unstimulated saliva samples were collected from 60 participants, 30 smokers and 30 non-smokers in Kuala Lumpur and Klang Valley, Malaysia. DNA extraction was performed using the Qiagen DNA mini kit, and the 16S rRNA bacterial gene was amplified and sequenced using the Illumina MiSeq platform. Sequencing reads were processed using DADA2, and the alpha and beta diversity of the bacterial community was assessed. Significantly differentiated taxa were identified using LEfSe analysis, while differentially expressed pathways were identified using MaAsLin2. Results A significant compositional change (beta diversity) was detected between the two groups (PERMANOVA P < 0.05). Specifically, the levels of phylum Firmicutes and genus Streptococcus were elevated in smokers, whereas phylum Proteobacteria and genus Haemophilus were depleted compared to non-smokers. At the species level, Streptococcus oralis, Streptococcus salivarius, and Streptococcus gingivalis were enriched in smokers. We observed significant differences in the abundance of thirty-seven microbial metabolic pathways between waterpipe smokers and non-smokers. The microbial pathways enriched in smokers were those implicated in polymer degradation and amino acid metabolism. Conclusion The taxonomic and metabolic profile of the salivary microbiome in waterpipe smokers compared to healthy controls exhibited a paradigm shift, thus, implying an alteration in the homeostatic balance of the oral cavity posing unique challenges for oral health.